Studi Kritis Buku Hazihi Lugati dan al-Muyassar fi Ilmin Nahwi di Pondok Pesantren Tahfizhul Qur'an Imam An-Nasa'i Gowa - Rappung, Hasriana; Ilyas, Hamka; Abd. Rahman, Anwar (Universitas Islam Negeri Alauddin, 2023)
This research discusses the critical study of Arabic textbooks at the Tahfizhul Qur'an Imam An-Nasa'i Gowa Islamic Boarding School at the wusta level, based on the achievement of four language skills. The aim of this research is to find out how the availability of teaching materials in the books Ha>z> Lugati> and al-Muyassar fi> 'Ilmin Nahwi fulfills the four language skills. This type of research includes library research with a qualitative descriptive analysis type. The data sources for this research are scientific literature, documents from interviews, observations, and other supporting data sources. Data is collected from references that are considered representative and from respondents who have a direct connection to the research. The data is then classified, selected and quoted according to its relevance to the problem being studied and then analyzed using a document study approach. The results of this research show, 1) The books